Reasons for aggressive classroom management and directions for change through teachers' professional development programmes. Issue 2 (14th March 2016) - Romi, Shlomo; Salkovsky, Merav; Lewis, Ramon (Rom)
Abstract: This investigation was designed to determine whether there are significant relationships between the reasons teachers provide for aggressive classroom management techniques and the type of professional education created to help them reduce their reliance on such techniques. The study reports data from a survey of 192 Australian teachers showing that teachers' gender and their school (primary or secondary) are related to rationales for teacher aggression. Teachers more accepting of the Attribution narrative as an explanation for teacher aggression are less likely to be supportive of gaining more knowledge about a misbehaving student. In contrast, those who more readily identify Efficacy as a reason for teacher aggression are more likely to gain more knowledge about a misbehaving student and about techniques that work with that student in other settings. Finally, teachers more accepting of the Attachment narrative did not exhibit a preference for any specific kind of support. Consequently, all types of PD activities might contribute to teachers who are seeking to feel close to students.